2020
DOI: 10.1016/j.jds.2019.12.003
|View full text |Cite
|
Sign up to set email alerts
|

The effect of implant neck microthread design on stress distribution of peri-implant bone with different level: A finite element analysis

Abstract: Background/purpose Significant research has proposed that the implant with microthread in the neck can significantly reduce marginal bone loss, but whether it is consistent in the condition of marginal bone loss is still unknown. The objective of this study is to investigate the effect of microthread on stress distribution in peri-implant bone with different bone level using finite element analysis. Materials and methods A series of computational models of mandible segm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…It has been suggested by finite element analysis (FEA), that the microthreaded design could lead to more compressive and less shear stress under off-axis loading and is less likely to pose a risk of MBL triggered by overloading [ 20 ]. However, the authors decided not to refer to such results for two reasons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested by finite element analysis (FEA), that the microthreaded design could lead to more compressive and less shear stress under off-axis loading and is less likely to pose a risk of MBL triggered by overloading [ 20 ]. However, the authors decided not to refer to such results for two reasons.…”
Section: Discussionmentioning
confidence: 99%
“…One of these modifications is addition of microthreads in the coronal part of implants [ 8 , 11 16 ]. As shown in finite element analysis studies, the microthraed design allows a better distribution of stress to the surrounding bone and may minimize the marginal bone loss (MBL) [ 17 20 ]. Several clinical studies have also demonstrated that rough surfaced implants with microthreads at the neck can better resist axial loads and preserve the marginal bone level during the healing period; therefore, resulting in less MBL under functional loading [ 6 , 7 , 11 , 21 23 ] But microthreads designed on implant neck surfaces have been reported to provide controversial clinical outcomes [ 12 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the area of implant reconstruction, there are researchers who investigated the effects of micro thread on stress distribution during bone pre-implantation using FEA. Different types of bones were constructed using several computational models of the human mandible with the simulation of bone resorption [15]. A healthy male mandibular bone was scanned using a cone-beam computed tomography where the acquired images were imported to Materialise-Mimics v17 software for further image processing and modelling.…”
Section: Bone Implantmentioning
confidence: 99%
“…In this approach, model data was acquired by non-contact laser systems, and it was implemented for dental and biomechanical applications. Jin et al 11 investigated the influence of micro-thread in peri-implant bone with a distinct level of bone using the numerical model. Moreover, they investigated the effect the micro-thread in peri-implant bone on stress distribution.…”
Section: Introductionmentioning
confidence: 99%